2011
DOI: 10.1111/j.1398-9995.2011.02706.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of interleukin‐32 in chronic rhinosinusitis with and without nasal polyps

Abstract: Background Chronic rhinosinusitis (CRS) is a heterogeneous disease characterized by local inflammation of the upper airways and sinuses and is frequently divided into polypoid CRS (CRSwNP) and non-polypoid CRS (CRSsNP). However, the mechanism of inflammation in CRS has still not been fully elucidated. The aim of the study was to investigate the role of IL-32, a recently discovered proinflammatory cytokine, in CRS. Methods We collected nasal epithelial cells and nasal tissue from patients with CRS and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…IL-32 plays an important role in innate and adaptive immune response, 17 and is involved in many inflammatory disorders, such as chronic rhinosinusitis. 7 Recently, it was reported that HBeAg induces the expression of IL-1b, granulocyte macrophage-colony stimulating factor (GM-CSF) and TNF-a in hepatocytes. 18 IL-1b or TNF-a increases the expression of IL-32 by human hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-32 plays an important role in innate and adaptive immune response, 17 and is involved in many inflammatory disorders, such as chronic rhinosinusitis. 7 Recently, it was reported that HBeAg induces the expression of IL-1b, granulocyte macrophage-colony stimulating factor (GM-CSF) and TNF-a in hepatocytes. 18 IL-1b or TNF-a increases the expression of IL-32 by human hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study 8 proved that IL-32 is an important cytokine involved in the inflammation of allergic rhinitis (AR). In that study, IL-32 expression is increased in the nasal mucosa of AR patients and the level of IL-32 expression in nasal mucosa tissue from AR patients correlates with inflammation, IL-1b, IL-18.…”
Section: Introductionmentioning
confidence: 99%
“…528 In addition to host defense molecules, ECs respond to PRR stimulation with the secretion of cytokines and chemokines that foster inflammation and attract and activate innate effector cells. 362,515,[529][530][531][532] In addition, the EC cytokines play a key role in shaping any subsequent adaptive immune response. Cytokine crosstalk between ECs, innate lymphoid cells (ILCs), and dendritic cells matches the appropriate innate and adaptive response to particular foreign stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the classification of CRS as either CRS with nasal polyps (CRSwNP) or CRS without nasal polyps (CRSsNP) (4). It has been demonstrated that the pro-inflammatory cytokine interleukin-32, is differentially expressed in the nasal epithelial cells of patients with CRSwNP and those with CRSsNP (5). Although the differential expression of inflammatory mediators in CRSwNP and CRSsNP has been previously demonstrated (6), further studies are required to provide a basis for the accurate diagnosis and the development of effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%